ONCE DAILY TREATMENT WITH SPARFLOXACIN IN COMPLICATED URINARY TRACT INFECTIONS: CLINICAL AND BASIC COMPARATIVE STUDIES ON MORNING AND EVENING REGIMENS - Kumon, Hiromi (CHEMOTHERAPY, 1992)
The efficacy and safety of sparfloxacin (SPFX), a new quinolone which can be administered once a day, were investigated in a double-blind comparative study to determine the effect of altering the time of administration. Differences in the pharmacokinetics depending on the time of administration and changes in the MIC values in nocturnal and diurnal urine were also examined. 1) A comparative study was performed by administering 300 mg of SPFX once a day after breakfast (group M) or after dinner (group E) for 5 days to noncatheterized patients with complicated urinary tract infections according to the criteria of the Japanese UTI Committee. Of a total 119 subjects, 49 in group M and 44 in group E were analyzed for efficacy. The overall clinical efficacy judged by the evaluation committee was 79.6% in group M and 63.6% in group E. The incidence of side effects was 5.1% in group M and 1.7% in group E. Both rates were higher in group M, but there were no significant differences between the groups. Group M also showed significantly greater efficacy in improving pyuria and greater overall clinical efficacy as evaluated by the attending physicians. 2) In a cross-over study performed in six healthy male volunteers, 300 mg of SPFX was administered after breakfast or after dinner for 5 days, the blood and urine levels of SPFX on the 1 st and 5 th day of administration were measured by HPLC, and the pharmacokinetics were compared. The Cmax Tmax T1/2, and AUC values and the urinary excretion rates of SPFX on the first and fifth days showed no significant differences between groups M and E. 3) The MIC of urine for standard bacterial strains, the urinary pH and the urinary concentration of metal ions were measured using the nocturnal and diurnal urine obtained from the six healthy male volunteers. The MIC values of urine for four standard strains of three bacterial species were markedly higher than those obtained in Mueller Hinton broth. In a comparison of the nocturnal and diurnal urine in the same subjects, the MIC was 1 to 3 tubes higher in five out of six cases and the urinary bivalent metal ion concentration was 2 to 5-fold higher in four out of six cases in the nocturnal urine. The above results suggest that differences in the MIC between nocturnal and diurnal urine could be responsible for differences in the efficacy of SPFX, depending on the timing of administration when it is used in the treatment of complicated urinary tract infections.